Health Tourism Facility Use of Digital Marketing and AI - David Vequist (Visions in Leisure and Business)
The proliferation of social media platforms has fundamentally reshaped patient acquisition strategies in health and wellness tourism, creating unprecedented opportunities for providers to engage with international patients across diverse digital channels. From boutique clinics in Mexico offering specialized dental, cosmetic, and bariatric procedures, to destination medspas providing aesthetic treatments, and even comprehensive global hospitals like the Mayo Clinic, healthcare providers are leveraging multi-platform social media strategies to attract and inform potential medical travelers. Research indicates that these digital marketing approaches now encompass a sophisticated array of content formats, including short-form video on TikTok, professional imagery on Instagram, long-form educational content on YouTube, and community- 44 building interactions on Facebook, Instagram, and X (formerly Twitter). The strategic use of social media transcends traditional marketing, providing patients with visual testimonials, procedural previews, physician introductions, and real-time engagement that demystifies medical travel experiences. According to recent studies, 68% of medical tourists now consult social media platforms as a primary or secondary source of information before making cross-border healthcare decisions, with visual and video content showing the highest engagement rates. In addition, artificial intelligence (AI) is increasingly being used by these organizations to reach more patients. This digital transformation enables healthcare facilities to overcome geographical barriers, build trust through transparent communication, and create targeted marketing campaigns that speak directly to specific patient demographics seeking international medical treatments.